(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
This paper deals with the analytical solutions of the fractional-order linear systems characterized by DX(t) = AX(t) fractional differential equations. Here D, is the fractional derivative in the Hattaf sense and A is the (2x2)-type non-singular real coefficient matrix. We present some results related to the existence of analytical solutions of the linear equation systems of the Hattaf fractional derivative. These solutions are provided for three different fractional-order linear systems.